Ignition Performance of New and Used Motor Vehicle Upholstery Fabrics - Spearpoint, Michael; Olenick, Stephen M; Torero, Jose L; Steinhaus, Thomas (Wiley InterScience, 2005)
This paper examines the standards for fire safety in transport systems and in particular the test method for the flammability of materials within passenger compartments of motor vehicles. The paper compares data from ignition tests conducted in the Cone Calorimeter and the FIST apparatus with tests conducted using the FMVSS 302 horizontal flame spread apparatus. Ten materials were selected as representative of those used as seat coverings of private and commercial passenger vehicles. The time to ignition of new and used materials subject to exposure heat fluxes between 20 kW/m2 and 40 kW/m2 was measured. The results from the ignition tests were analyzed using thermally thick and thermally thin theoretical models. The critical heat flux for sustained piloted ignition was determined from the time to ignition data using the thermally thin approach. Derived ignition temperatures from both the thermally thick and thermally thin methods were compared with measurements using a thermocouple attached to the back surface of materials in selected tests. The flame spread rates in the FMVSS 302 apparatus were determined and a comparison was made between the performance of the materials in the flame spread apparatus, the Cone Calorimeter and the FIST. The results suggests that a critical heat flux criterion could be used to provide an equivalent pass/fail performance requirement to that specified by the horizontal flame spread test although further testing is needed to support this.
Keywords: fire safety; critical heat flux